2020
DOI: 10.3390/agronomy10030375
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Interactions between Grassland Ecosystem Soil and Plant Properties under Long-Term Mineral Fertilization

Abstract: Grasslands intensification by use of mineral fertilization has contributed substantially to the increase in forage production. Intensification, however, can degrade the other beneficial functions or soil properties. The effects of mineral fertilization on soil and plant chemical qualities of a permanent wet grassland (Festucetum pratense association) were investigated in Slovakia. The grassland was treated using 3 different N, P, and K rates of mineral fertilizers in kg. ha−1. yr−1 plus the Control (0NPK) almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…With regard to the discussed factors of grassland degradation, it should be emphasised that studies conducted by various authors prove that there is a positive relationship between the SOC content in grassland soils and their pH [KARABCOVÁ et al 2015], the state of humidity [KERR, OCHSNER 2020;TIAN et al 2016], and the level of fertilisation [VARGOVÁ et al 2020].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the discussed factors of grassland degradation, it should be emphasised that studies conducted by various authors prove that there is a positive relationship between the SOC content in grassland soils and their pH [KARABCOVÁ et al 2015], the state of humidity [KERR, OCHSNER 2020;TIAN et al 2016], and the level of fertilisation [VARGOVÁ et al 2020].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the discussed factors of grassland degradation, it should be emphasized that studies conducted by various authors prove that there is a positive relationship between the Corg content in grassland soils and their pH [46], the state of humidity [47,48], and the level of fertilization [49].…”
Section: [Table 13]mentioning
confidence: 99%
“…Messiga et al [15] found that phosphorus in the soil was increased by the application of P fertilizers, and soil pH was decreased by N application, which also affected the availability of exchangeable cations, while total carbon was not affected by either N or P fertilization. In a long-term experiment in a wet grassland under different NPK fertilization treatments [16], the results showed that land use was more important in soil acidification than fertilizers themselves. According to the same study, organic soil carbon and available K fluctuated substantially according to fertilizer rates, while total nitrogen, C:N ratio and available P showed less dramatic changes.…”
Section: Introductionmentioning
confidence: 97%